Breaking Barriers: Understanding Mental Health Care Disparities in Latino and African American Populations - Bianca Taylor; Karla Collazo Melian; Grettel Castro; Nathaly Desmarais (Journal of Racial and Ethnic Health Disparities, 2026)
Abstract Aims This study examines disparities in mental health service access and unmet need among Non-Hispanic Black and Hispanic adults compared to Non-Hispanic White adults in the United States. Methods This pooled cross-sectional analysis examined racial and ethnic disparities in mental healthcare access and unmet need. We utilized data from the National Survey on Drug Use and Health (NSDUH), an annual cross-sectional survey conducted by the Substance Abuse and Mental Health Services Administration (SAMHSA) providing nationally representative data on substance use, mental health, and healthcare utilization among the U.S population aged 12 years and older, pooling data from 2019 to 2021, analyzing 25,892 adults aged 18 years and older who identified as Non-Hispanic White, Non-Hispanic Black, or Hispanic. Race/ethnicity served as the independent variable. Two outcomes were assessed independently: (1) received mental healthcare in the past 12 months and (2) unmet perceived need for mental healthcare. Binary logistic regression models adjusted for age, sex, insurance status, employment, family income, and geographic location. Results Descriptive analyses showed Non-Hispanic White participants had higher rates of receiving mental healthcare (79.8%) compared to Non-Hispanic Black (71.3%) and Hispanic (67.6%) participants. Conversely, minority participants reported higher rates of unmet perceived need: Hispanic (54.4%), Non-Hispanic Black (48.6%), and Non-Hispanic White (41.2%). Adjusted analyses confirmed these patterns: Non-Hispanic Black and Hispanic participants had significantly lower odds of receiving mental healthcare (Non-Hispanic Black: OR = 0.63, 95% CI = 0.56–0.70; Hispanic: OR = 0.65, 95% CI = 0.60–0.71) compared to Non-Hispanic White participants. For unmet need, both Non-Hispanic Black (OR = 1.24, 95% CI = 1.13–1.38) and Hispanic participants (OR = 1.31, 95% CI = 1.21–1.42) had significantly higher adjusted odds. The addition of sex to the adjusted models did not alter the race/ethnicity associations; female sex was independently associated with higher odds of both receiving care (OR = 1.09, 95% CI = 1.02–1.17) and reporting unmet perceived need (OR = 1.26, 95% CI = 1.19–1.33). Conclusions These findings highlight a persistent pattern in mental healthcare disparities during the COVID-19 pandemic period (2019–2021). Both Non-Hispanic Black and Hispanic adults faced significant barriers to receiving care, with lower odds of service receipt and higher odds of unmet need. Policy initiatives must address structural barriers to access, including insurance coverage gaps, workforce shortages in minority serving communities, cultural and linguistic barriers, and structural racism in healthcare systems.